2008
DOI: 10.1002/mds.21966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of desipramine and citalopram treatments for depression in Parkinson's disease: A double‐blind, randomized, placebo‐controlled study

Abstract: Depression is one of the most common psychiatric disturbances in Parkinson's disease (PD). Recent reviews have highlighted the lack of controlled trials and the ensuing difficulty in formulating recommendations for antidepressant use in PD. We sought to establish whether antidepressants provide real benefits and whether tricyclic and selective serotonin reuptake inhibitor (SSRI) antidepressants differ in their short-term efficacy, because the time to onset of therapeutic benefit remains an important criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
184
1
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(201 citation statements)
references
References 35 publications
3
184
1
13
Order By: Relevance
“…They were wellestablished to have clinical efficacy in treating syndromic depression in physically healthy populations, but their effectiveness in PD has also been shown in a small number of controlled studies. 33,36 However, TCAs pose several clinical difficulties that make them less than preferable for clinical use as a first-line agent for depression (although they were used very successfully for many years in medically healthy, depressed patients). In particular, their side effect profile is unfavorable; anticholinergic side effects can be a burden to the patient, and it can also increase the risk of delirium in this vulnerable population.…”
Section: Tricyclic Antidepressants (Tcas)mentioning
confidence: 99%
“…They were wellestablished to have clinical efficacy in treating syndromic depression in physically healthy populations, but their effectiveness in PD has also been shown in a small number of controlled studies. 33,36 However, TCAs pose several clinical difficulties that make them less than preferable for clinical use as a first-line agent for depression (although they were used very successfully for many years in medically healthy, depressed patients). In particular, their side effect profile is unfavorable; anticholinergic side effects can be a burden to the patient, and it can also increase the risk of delirium in this vulnerable population.…”
Section: Tricyclic Antidepressants (Tcas)mentioning
confidence: 99%
“…56,57 Despite this, most PD patients with depression are generally prescribed an SSRI, 58 likely because of its adverse effect profile. Pramipexole, used to treat motor symptoms in PD, also appears to have an antidepressant effect.…”
Section: Depressionmentioning
confidence: 99%
“…In clinical practice many clinicians use SSRI drugs because of their good tolerability although tremor, akathisia and Parkinsonism may be worsened. Citalopram has shown some efficacy, albeit less than desipramine in a shortterm controlled trial [Devos et al 2008], but more recently nortriptyline demonstrated efficacy in PD depression while controlled-release paroxetine did not [Menza et al 2009]. In patients receiving a monoamine oxidase (MAO)-B inhibitor (such as selegiline) caution is needed with SSRI drugs because of a potential, but rare interaction that can precipitate serotonin syndrome [Richard et al 1997].…”
Section: Depressionmentioning
confidence: 99%